2016
DOI: 10.4330/wjc.v8.i12.703
|View full text |Cite
|
Sign up to set email alerts
|

Hematological disorders and pulmonary hypertension

Abstract: Pulmonary hypertension (PH), a serious disorder with a high morbidity and mortality rate, is known to occur in a number of unrelated systemic diseases. Several hematological disorders such as sickle cell disease, thalassemia and myeloproliferative diseases develop PH which worsens the prognosis. Associated oxidant injury and vascular inflammation cause endothelial damage and dysfunction. Pulmonary vascular endothelial damage/dysfunction is an early event in PH resulting in the loss of vascular reactivity, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 175 publications
(165 reference statements)
3
25
0
2
Order By: Relevance
“…Furthermore, pulmonary vascular endothelial dysfunction is an important initiating factor in the development of PH 37. Our data showed that IL-17 significantly enhanced the angiogenesis of PAECs, which is consistent with the observation of Numasaki et al 38.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, pulmonary vascular endothelial dysfunction is an important initiating factor in the development of PH 37. Our data showed that IL-17 significantly enhanced the angiogenesis of PAECs, which is consistent with the observation of Numasaki et al 38.…”
Section: Discussionsupporting
confidence: 93%
“…This case is consistent with what is known regarding chronic myeloproliferative disorders associated with pulmonary hypertension, whereby there are multiple attributable causes described [41], similar to the noted heterogeneous etiologies of pulmonary hypertension after treatment with bone marrow transplant [42,43]. …”
Section: Pulmonary Hypertension and Myeloid Cell Disorderssupporting
confidence: 89%
“…Pulmoner hipertansiyonun patofizyolojisi ile ilgili çeşitli teoriler mevcuttur. Endotelyal disfonksiyona bağlı doku hipoksisi, anemiye bağlı yüksek kardiyak output ve demir birikimine bağlı oksidatif doku hasarı nedeniyle pulmoner vasküler remodelling gibi çeşitli mekanizmalar öne sürülmüştür [5] . Gerek talasemi intermediada gerekse talasemi majörde eski çalışmalar pulmoner hipertansiyon sıklığının %65-70 arasın-da olduğu bildirse de [6,7] daha yeni çalışmalarda bu oranın %10'larda olduğu görülmektedir [8] .…”
Section: Discussionunclassified